2020
DOI: 10.3389/fphar.2020.507113
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Metabolomics Reveals Protection of Taohong Siwu Decoction Against Abnormal Uterine Bleeding

Abstract: Incomplete abortion, a procedure for terminating pregnancy, will lead to abnormal uterine bleeding (AUB), infections, and even death. Taohong Siwu decoction (TSD) is a traditional Chinese medicine (TCM) formula, which has been developed to treat AUB for hundreds of years. However, the mechanism of the protective effect of TSD against AUB is not clear. We performed mass spectrometry (MS) of uterine samples to observe metabolic profile resulting from the treatment with TSD. An integrated gas chromatography-mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The inheritance and innovation of modern physicians has widely used THSWD in the treatment of various systems throughout the body, and has been widely used in TCM clinics. THSWD is traditionally used in gynecology, the effective rate of treating primary dysmenorrhea is more than 90% [ 20 ], and it can be used for postpartum blood stasis [ 21 ], uterine bleeding [ 22 ], etc. It is widely used in internal medicine such as coronary heart disease [ 23 , 24 ], ischemic stroke [ 25 ], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inheritance and innovation of modern physicians has widely used THSWD in the treatment of various systems throughout the body, and has been widely used in TCM clinics. THSWD is traditionally used in gynecology, the effective rate of treating primary dysmenorrhea is more than 90% [ 20 ], and it can be used for postpartum blood stasis [ 21 ], uterine bleeding [ 22 ], etc. It is widely used in internal medicine such as coronary heart disease [ 23 , 24 ], ischemic stroke [ 25 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used to treat many gynecological diseases caused by blood deficiency and blood stasis, such as dysmenorrhea, breast hyperplasia, ovarian cysts, menopausal syndrome, etc. [ 20 , 22 ]. Clinical studies have found that THSWD can treat breast cancer by reducing blood vessel and lymphangiogenesis with auxiliary chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The LS-MS results showed that TWS decoction contained ferulic acid and amygdalin, and their relative peak areas were 1,562,890 and 33,370, respectively. Previous studies indicated that the main active ingredients of TSW decoction were ferulic acid, paeoniflorin, amygdalin, hydroxysafflor yellow A, catalpol, and gallic acid [ 26 , 27 ]. Therefore, we speculated that the main active components of TSW decoction were ferulic acid and amygdalin.…”
Section: Resultsmentioning
confidence: 99%
“…TCM compounds have multi-target and multi-pathway biological effects. As a traditional classic prescription, THSWD is currently widespread in the elds of internal medicine, surgery, gynecology, and orthopedics [10,11]. It is widely used in clinical practice for cardiovascular diseases [12], osteoporosis and bone fracture [13][14][15][16] and exhibits excellent therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%